(untitled) (Medico Legal Update, 2020)
The COVID-19 virus, emerged at the end of 2019 began threatening the health and lives of millions of people within few weeks. At present all regions of the world, declared lockdown for controlling highly contagious and pandemic virus. During this lockdown period people are restricted to stay at home, for few weeks. During the idle stay at home for very long hours, will cause mental health problems, like stress, fear, anxiety, depression and sleep problems. In this present study, the researcher, made an attempt to study the impact on mental health of individuals during the lockdown period. The basic aim of this study: is to find out the viz. “Mental health problems” and its influence on ‘Gender, Age, Marital status and Occupation’ differences. The data has been collected through online questionnaire and analyzed using “one way analysis of variance”, t-test and Correlation. The study found that significant mental health problems attributed more in female than male folk. There is significant social dysfunction in female than male. Middle age group i.e. (30-44) have more stress and pressure of future and job shortening are creating depression.